Can a large-mesh sieve panel replace or supplement the Nordmøre grid for bycatch mitigation in the northeast Atlantic deep-water shrimp fishery? - Jacques, Nadine; Herrmann, Bent; Larsen, Roger B.; Sistiaga, Manu Berrondo; Brčić, Jure; Gökçe, Gökhan; Brinkhof, Jesse (Fisheries Research, 2019)
Source at https://doi.org/10.1016/j.fishres.2019.105324. The Nordmøre grid is the principle bycatch mitigation device in many shrimp trawl fisheries. However, in several of these fisheries, bycatch is a problem because small sized fish can pass through the grid and enter the codend together with the targeted shrimp. One such fishery is the Northeast Atlantic deep-water shrimp ( Pandalus borealis ) fishery, where the use of a Nordmøre grid is mandatory. In this fishery, redfish ( Sebastes spp.) and polar cod ( Boreogadus saida ) are two common bycatch species. Redfish is a commercially important species that at times is captured in great numbers, whereas polar cod is a threatened species that can also be caught in high numbers. Sieve panels are bycatch reduction devices commonly used in shrimp fisheries and their potential to replace or supplement the Nordmøre grid in the Northeast Atlantic deep-water shrimp fishery is of interest. We investigated the size selectivity of redfish, polar cod and deep-water shrimp for the Nordmøre grid and four sieve panel configurations differing in mesh size (182 and 286 mm) and inclination angle (10 and 20°). The sieve panels were unable to replace the Nordmøre grid as a stand-alone device due to greater catches of the bycatch species. However, combining the two devices provided promising results. Specifically, when a large-mesh sieve panel was placed in front of the Nordmøre grid, 20–40% fewer small redfish and polar cod in a specific size range entered the codend, while the loss of targeted shrimp was less than 5%.